2017
DOI: 10.1039/c6ay02949c
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive poisoning-resistant optical carbon dioxide sensors for environmental monitoring

Abstract: Resistivity of optical carbon dioxide chemosensors towards poisoning by acidic gases is significantly improved by using an additional perfluorinated polymer coating making the sensors suitable for long-term measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 71 publications
(60 reference statements)
2
25
0
Order By: Relevance
“…Clarke et al (2015) demonstrated a corresponding positive sigmoidal relationship between R and pH. The optode shows a temperature dependence (Figure 3), which has also been reported for other optical chemical sensors by Clarke et al (2015) and Fritzsche et al (2017). The observed patterns in our study are consistent with the previous work and are in line with thermodynamic considerations dictating temperature influences on the indicator acid dissociation constant, as well as changes to the indicator fluorescence intensity and the permeability of the membrane.…”
Section: Optode Characterization Pco 2 Calibration Of Optodesupporting
confidence: 82%
See 1 more Smart Citation
“…Clarke et al (2015) demonstrated a corresponding positive sigmoidal relationship between R and pH. The optode shows a temperature dependence (Figure 3), which has also been reported for other optical chemical sensors by Clarke et al (2015) and Fritzsche et al (2017). The observed patterns in our study are consistent with the previous work and are in line with thermodynamic considerations dictating temperature influences on the indicator acid dissociation constant, as well as changes to the indicator fluorescence intensity and the permeability of the membrane.…”
Section: Optode Characterization Pco 2 Calibration Of Optodesupporting
confidence: 82%
“…A three dimensional fit to calibration results yielded a first by second degree polynomial (SSE = 0.081, R 2 = 0.99, Equation 3, Table 1), in agreement with previous optical pCO 2 sensor work (Atamanchuk, 2013;Atamanchuk et al, 2014;Fritzsche et al, 2017). Where B, C, D, and E are the slopes, A is the offset (as listed in Table 1), R is the ratio value from Equation (1) and T is the in situ temperature.…”
Section: Optode Characterization Pco 2 Calibration Of Optodesupporting
confidence: 67%
“…One way to avoid the additional complexity of pumping is to use fluorescent lifetime based measurements that have reduced sensitivity to the signal intensity. This technology has been successfully developed for dissolved O 2 sensors (Körtzinger et al, 2005;Tengberg et al, 2006;Takeshita et al, 2013), while similar technology for pH and pCO 2 has proven more challenging but recent developments show promise in field deployments (Atamanchuk et al, 2014;Clarke et al, 2015;Fritzsche et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, this evaluation becomes ambiguous in the presence of DOM and H 2 S because both contribute to A T (Kuliński et al ; Yang et al ) and this contribution is not accounted for in the available software for CO 2 ‐system calculations, e.g., CO 2 sys (Pierrot et al ). In addition, analytical techniques to determine the pCO 2 of discrete samples are not well developed and optical pCO 2 sensors are prone to poisoning by H 2 S (Atamanchuk et al ; Fritzsche et al ). Consequently, A T and pCO 2 are often not accessible for an overdetermination of the CO 2 system.…”
mentioning
confidence: 99%